Man against the elements of nature: from the pages of Aleksandr Kuprin’s works - Szymonik, Danuta (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The topic of this paper is discussed on the basis of two stories, ‘The Bog’ (‘Boloto,’ 1903) and ‘The Black Lightning’ (‘Chernaya molnia,’ 1913), and the short story cycle ‘The Laestrygonians’ (‘Listrigony’, 1911) by an eminent Russian writer of the turn of the 20th century, Aleksandr Kuprin. The stories bring images of the four basic natural elements – earth, fire, water and air. In particular, in ‘The Laestrygonians’ Kuprin shows the power of the sea, combined with the unimaginable force of the wind. The author presents man fighting a one-sided battle with the forces of nature. There are, as well, obvious analogies between the four elements and the elemental aspect of human nature. The stories under analysis not only depict the most important elements of the natural world, but also have particular social overtones.